Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum DSM 11520 for horses, dogs, cats and pet rabbits (Animal Probiotics Sweden AB) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on Lactiplantibacillus plantarum DSM 11520 when used as a technological additive (acidity regulator) in feed for horses, dogs, cats and pet rabbits. The additive is intended to be incorporated into oat‐derived products (ca. 55% moisture content), carrot root‐derived products (≥ 90% moisture) and coconut flesh‐derived products (≥ 90% moisture) at a minimum inclusion level of 8.0 × 1010 CFU/kg of the feed material under scope. The bacterial species L. plantarum is considered by EFSA to be suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the strain has been clearly established and it did not show acquired resistance to antibiotics of human and veterinary importance. The FEEDAP Panel concluded that the use of this strain in animal nutrition is safe for the target species, consumers of horse meat and the environment. Regarding the user safety, the additive Lactiplantibacillus plantarum DSM 11520 is not irritant to skin or eyes in the product tested containing maltodextrin and oat bran as carriers, but owing to its proteinaceous nature, it should be considered a respiratory sensitiser. No conclusions can be drawn on the skin sensitisation potential of the additive. The FEEDAP Panel concluded that incorporation of Lactiplantibacillus plantarum DSM 11520 at a minimum concentration of 8.0 × 1010 CFU/kg into oat‐derived products (ca. 55% moisture content), carrot root‐derived products (≥ 90% moisture) and coconut flesh‐derived products (≥ 90% moisture) has the potential to reduce the pH of these feedingstuffs.